Line of Sight(LoS) Probability Prediction for Satellite and HAPs Communication in Trabzon, Turkey - Volkan Aydın; Ismail Hakkı Çavdar; ZEYNEP HASIRCI (International Journal of Applied Methods in Electronics and Computers, 2016)
The knowledge of Line of Sight (LoS) probability is curicial to estimate signal attenuation correctly in mobile wireless communication. Especially in built-up areas, more accurate LoS probability determination helps to obtain more realistic propagation models or path loss models. Geographic Information Systems (GIS) and City Information Systems (CIS) are used to provide a necessary data to calculate the LoS probability. In this study, LoS analyzes are made via Arcgis software for the most well-known streets in Trabzon, Turkey. For these analyzes, the Earth''s surface is accepted as flat and a simple geometrical approach is used for calculations in this paper. A Matlab algorithm was created to calculate LoS probability depending on the elevation angle which is an important parameter for satellite services. LoS probability vs. elevation angle is presented for interested streets. As a result, LoS probability for Trabzon dependent elevation angle is estimated and presented.